Conocimiento moral y justificación moral de la acción - Garreta, Mariano (2019)
“Moral Knowledge and the Moral Justification of Action”. The cost of making a decision on the basis of false beliefs varies according to different contexts of action. In some cases, the cost of the error could be very high for the wellbeing of the agents involved, while in others it might be very low. The contrast between these two types of contexts has recently been a focus of attention in epistemology.My aim in this article is to apply to the moral field the analysis of some of the implications from that contrast. In particular, I will defend the thesis that there are cases in which a subject may know fallibly that a course of action is best from a moral point of view. Despite which, however, he may not be justified to act on the basis of that knowledge in the context in which he is situated, given the high cost involved if the judgment was false. Therefore, in such cases, there would be a gap between the concepts of moral knowledge and the moral justification for an action.